English Needs Analysis for Sharia Bank Employees - Novita Kusumaning Tyas; Athiya Salwa (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2021)
The purpose of this study was to look into the English needs of Sharia bank employees in Semarang, Central Java. Qualitative research was used as the design research of this research. The subject of this research was 30 bank employees in one sharia bank in Semarang. Research data was collected by using interviews and questionnaires. The result of this research showed that: (1) Speaking and listening skills are more needed in their work especially as customer service than reading and writing skills; (2) Sharia bank employees also need English material especially in the terms of banking, accounting, and also computer programs. The employees need more about special terms relate to their jobs. Besides that, they also need skills in writing business correspondence for back-office positions.